2009
DOI: 10.1068/a41245
|View full text |Cite
|
Sign up to set email alerts
|

Placing Power in the Creative City: Governmentalities and Subjectivities in Liberty Village, Toronto

Abstract: In this paper we analyze the making of Liberty Village as a creative hub in inner-city Toronto. We focus on the role of property developers and the Liberty Village Business Improvement Association in fostering the area's internal economic geography. Drawing on the literature on governmentality, we dissect how the production of a place identity requires both the production of new subjectivities and the exclusion of alternative actors and understandings of organization within the district.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…One important point must be made at the outset: what can be understood as a governmentality analysis need not encompass all the anchor points delineated here, which are culled from a wide variety of Foucault's scholarship over time and thus reflect different concerns he had over the course of his career. There are rigorous analyses of the governance of populations that do not engage, for example, resistance or the development of a transformational mentality (e.g., Hannah 2000;Raco 2003;Watts 2003;O'Grady 2004;Dodge and Kitchin 2005;Rose-Redwood 2006), whereas others do (e.g., Cameron 1998;Cooper 2006;Mitchell 2006;Crowley and Kitchin 2008); some analyses focus on clarifying the genealogy of a mentality (e.g., Cruikshank 1999) and others emphasize pertinent mentalities that underscore on-the-ground practices (Rojas 2004) or the specification of techniques of power that ground mentalities (e.g., Hughes 2001;Larner and LeHeron 2004;Huxley 2006;Catungal and Leslie 2009). Other studies call attention to regimes of practices as a clearer avenue of analysis in comparison to those that focus on ideology (Barry 2004).…”
Section: Foucault On the Discipline Of Geographymentioning
confidence: 97%
“…One important point must be made at the outset: what can be understood as a governmentality analysis need not encompass all the anchor points delineated here, which are culled from a wide variety of Foucault's scholarship over time and thus reflect different concerns he had over the course of his career. There are rigorous analyses of the governance of populations that do not engage, for example, resistance or the development of a transformational mentality (e.g., Hannah 2000;Raco 2003;Watts 2003;O'Grady 2004;Dodge and Kitchin 2005;Rose-Redwood 2006), whereas others do (e.g., Cameron 1998;Cooper 2006;Mitchell 2006;Crowley and Kitchin 2008); some analyses focus on clarifying the genealogy of a mentality (e.g., Cruikshank 1999) and others emphasize pertinent mentalities that underscore on-the-ground practices (Rojas 2004) or the specification of techniques of power that ground mentalities (e.g., Hughes 2001;Larner and LeHeron 2004;Huxley 2006;Catungal and Leslie 2009). Other studies call attention to regimes of practices as a clearer avenue of analysis in comparison to those that focus on ideology (Barry 2004).…”
Section: Foucault On the Discipline Of Geographymentioning
confidence: 97%
“…Foucault's work on governmentality thus foregrounds techniques and practices of government and the modes of subjectivity constituted through governmental projects (Catungal and Leslie, 2009;Dean, 1999;Foucault, 1982;Grundy and Boudreau, 2008;Leslie and Rantisi, 2006;Rose, 1999). In the current era, government is particularly focused on cultivating the capacities of individuals to govern themselves (Boudreau et al, 2009;Dean, 1999;Larner, 2000).…”
Section: Policy Imperatives In the Neoliberal Citymentioning
confidence: 98%
“…Not only are subjects constructed in more entrepreneurial, responsible, and selfdisciplining ways, but they are also encouraged to mobilize their creative capacities to stimulate greater innovation and global competitiveness (Barnes et al, 2006;SECURING THE NEOLIBERAL CITY 1173Boudreau et al, 2009Catungal and Leslie, 2009;Fougère and Solitander, 2010;Grundy and Boudreau, 2008;Leslie and Rantisi, 2006;Ponzini and Rossi, 2010). For example, creative initiatives often attempt to foster subjectivities based on collaboration and networking (Catungal and Leslie, 2009).…”
Section: Policy Imperatives In the Neoliberal Citymentioning
confidence: 99%
“…Urban spaces labelled as 'creative', and their relationship to the delivery of economic, social and cultural policies, has been a subject of much scrutiny (Pratt, 2009, Jayne, 2005, Catungal and Leslie, 2009, Mommaas, 2004. The use of place-marketing strategies based, for example, on the exploitation of cultural attractions, mega-events and 'cultural quarters' to redevelop urban spaces has been a visible process, both in the West (Garcia, 2004a, 2004b, Evans, 2003, Balibrea, 2001, Rantisi and Leslie, 2006 and further afield (Lee, 2006, Yue, 2006, Hui, 2006.…”
Section: Organising Artistic Spaces In Urban Areasmentioning
confidence: 99%
“…It has been suggested, for example by Ley (2003), that the artists' role in this process is not only one of promoting investment or inward migration through making an area fashionable, but also in changing the dispositions of the urban population, for the artist's very presence, the deployment of a critical aesthetic disposition on the streets of old neighbourhoods, has become a principal tool for goading on gentrification, thereby lining with gold the pockets of buyers and sellers in the inner-city property market (Ley, 2003(Ley, p. 2542 This has led to a planning process that values some urban spaces on the basis of the everyday cultural activities of its residents, but whose aim is ultimately to stimulate consumption (Evans, 2005). Catungal and Leslie (2009) have consequently suggested that "the recent focus on culture and creativity is not all that divergent from older entrepreneurial models of urban governance" and that in the creative city agenda "as in entrepreneurial regimes, the emphasis is on attracting investment and tourists through the construction of spectacular spaces of consumption" (Catungal andLeslie, 2009 p. 2578). In the UK this phenomenon has been contextualised within the rise of creative industries policies during Labour's tenure in government between 1996 and 2010.…”
Section: Organising Artistic Spaces In Urban Areasmentioning
confidence: 99%